Patient monitoring system using power line carrier communication - NiranjanKumar, R; Praveen Kumar, G; Nirmal Kumar, S; Vibin, V (International Journal of Engineering and Technology, 2018)
Detection of changes due to movement in a real time video is very important tool. Patient movement & monitoring system is a system that is used to detect movement changes in patient. Those changes may be either abnormal behavior or unusual changes made by the patient in the absence of doctor. This paper presents the method of patient movement monitoring system for those patients that are taking medical treatment in both local and foreign hospitals with the help of frames comparison approach. In this project flex sensors are fixed in two hands of the patient when there is any movement in hands the sensor send information to the doctors by wireless communication. Glass setup with eye ball sensor is fixed in the patientâ€™s eye when any motions in the eye the sensor sense the value and send information to the doctor. Mems is used to find the patients leg movement and all the information is wirelessly transferred through PLC communication module and monitored in PC. Heartbeat and the temperature sensors are used to find the heart rate and the temperature of the patient.Â Â
Keywords: Carrier Spread Multiple Spectrum; Ethernet Card; Orthogonal Frequency Division Multiplexing; PLC-Power Line Communication Carrier; Spread Spectrum.